2006
DOI: 10.1124/jpet.106.102699
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Enzymatic Activity of Heme Oxygenases by Azole-Based Antifungal Drugs

Abstract: Ketoconazole (KTZ) and other azole antifungal agents are known to have a variety of actions beyond the inhibition of sterol synthesis in fungi. These drugs share structural features with a series of novel heme oxygenase (HO) inhibitors designed in our laboratory. Accordingly, we hypothesized that therapeutically used azole-based antifungal drugs are effective HO inhibitors. Using gas chromatography to quantify carbon monoxide formation in vitro and in vivo, we have shown that azole-containing antifungal drugs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 35 publications
(34 reference statements)
0
18
0
Order By: Relevance
“…The competitive HO inhibitor tin protoporphyrin IX (SnPP; (Drummond and Kappas, 1981) and the non-competitive HO inhibitor ketoconazole (Keto; Kinobe et al, 2006), both damped SCN PER2∷LUC rhythms relative to controls (Figs. 4 and S2; p’s < .05).…”
Section: Resultsmentioning
confidence: 99%
“…The competitive HO inhibitor tin protoporphyrin IX (SnPP; (Drummond and Kappas, 1981) and the non-competitive HO inhibitor ketoconazole (Keto; Kinobe et al, 2006), both damped SCN PER2∷LUC rhythms relative to controls (Figs. 4 and S2; p’s < .05).…”
Section: Resultsmentioning
confidence: 99%
“…One interesting aspect is the fact that the bacterial HO inhibitors identified by Furci et al (2007) bear close structural similarities to some of the imidazole-based inhibitors of mammalian HO activity characterised in our laboratory (Vlahakis et al 2005;Kinobe et al 2006a). Moreover, these imidazole-based mammalian and bacterial HO inhibitors are also structurally similar to azole-based antifungal drugs, including ketoconazole, sulconazole, and terconazole, which were identified as potent inhibitors of mammalian HO-1 and HO-2 (Kinobe et al 2006b). Because the inhibition of HO-1 and HO-2 activity by the imidazole-based antifungal drugs was observed at therapeutically relevant concentrations, it is plausible that inhibition of mammalian HO activity may play a role in some of the pharmacologic actions of these antimycotic drugs.…”
Section: Ho Activity In Infectionsmentioning
confidence: 92%
“…To block HO-activity during curcumin + NAC treatment we used the previously described specific non-porphyrin HO-activity inhibitor QC-15 at a dose of 50 μM [22, 23]. Since we observed that 50-μM SnMP in combination with 25-μM curcumin affected HO-1 expression and therefore could act as a possible confounder, we opted for the QC-15 inhibitor to study the effect of HO-activity in all experiments where 25-μM curcumin was used.…”
Section: Methodsmentioning
confidence: 99%